Molecular Docking Studies on a Series of Chalcone Derivatives Towards Possible Pharmacological Agents - Anandam, Rambabu; Ala, Vasu Babu; K, Bala Murali Krishna; Kasturi, Jyothi K; Trripuram, Vijaya Durga; Thota, Parvathi; Uppuluri, Anitha; Varala, Ravi; Bollikolla, Hari Babu (Pharmaceutical Science: New Insights and Developments Vol. 6, 2025)
The study of binding modes by molecular docking simulations suggested that these ligands may act by interacting with the predictive allosteric active site of the soybean lipoxygenase (PDB: 1RRH) instead of the metal binding site. An In Silico study was carried out on a series of chalcone ligands to understand their binding pattern with various molecular targets and to evaluate the possible pharmacological potency with relevance to their literature reports. In order for this, molecular docking was carried out on the active molecules against IMPDH and PARP1 enzymes to find out their binding pattern. The analysis was done by testing ligands against various molecular targets like 1PAX, 4OQA, 3WIL, 1FCZ, 2ZBH, 1YQT, 1SRE and 1ME7 for various cancers, HIV, Immunotherapy, Viral infection, inflammation, etc. The synthesised compounds were screened for possible anti-cancer activity on the A549 cell line (lung adenocarcinoma cell line) and anti-tuberculosis activity on the Mycobacterium tuberculosis strain. Further, molecular docking was also carried out on the active molecules against IMPDHand PARP1 enzymes to find out their binding pattern.